Hydrogen-enhanced fatigue crack growth behaviors in a ferritic Fe-3wt%Si steel studied by fractography and dislocation structure analysis. (22nd February 2019) - Wan, Di; Alvaro, Antonio; Olden, Vigdis; Barnoush, Afrooz
Abstract: The effect of hydrogen (H) on the fatigue behavior is of significant importance for metallic structures. In this study, the hydrogen-enhanced fatigue crack growth rate (FCGR) tests on in-situ electrochemically H-charged ferritic Fe-3wt%Si steel with coarse grain size were conducted. Results showed strong difference between the H-charged and the non-charged conditions (reference test in laboratory air) and were in good agreement with the results from literature. With H-charging, the fracture morphology changed from transgranular (TG) type to "quasi-cleavage" ("QC"), with a different fraction depending on the loading frequency. With the help of electron channeling contrast imaging (ECCI) inside a scanning electron microscope (SEM), a relatively large area in the failed bulk specimen could be easily observed with high-resolution down to dislocation level. In this work, the dislocation sub-structure immediately under the fracture surfaces were investigated by ECCI to depict the difference in the plasticity evolution during fatigue crack growth (FCG). Based on the analysis, the H-enhanced FCG mechanisms were discussed. Highlights: In-situ electrochemical hydrogen charging enhances the FCGR by up to 1000x. Transgranular, intergranular and "quasi-cleavage" features are identified. The enhanced FCGR is related to the area fraction of "quasi-cleavage" features. The dislocation cell formation is restricted in the hydrogen-charged cases.